Internet Lexicography: An Introduction - Klosa-Kückelhaus, Annette (Lexicographica. Series Maior, 2024)
The Internet has become the most important platform for lexicographic content. In this volume, lexicographers and researchers introduce the central aspects of Internet lexicography and present the current state of scientific research and lexicographic practice. Chapters cover key aspects of dictionary creation, such as the technical framework, the lexicographic process, access structures, automatic data collection, and user participation.